Three-dimensional transvaginal ultrasound: clinical implementation in assessing uterine cavity - Tammam, Abdelaziz E.; Khodry, Mostafa M.; Elnagar, Shymaa M. A.; Abdella, Ahmed H.; Taha, Sayed A. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Three-dimensional transvaginal ultrasonography (3D TVS) represents a new technique of imaging and provides a unique diagnostic tool for non-invasive examination of the uterine morphology and diagnosis of congenital uterine anomalies. In this study the clinical value of 3D TVS in diagnosis of uterine cavity abnormalities were evaluated. Methods: A prospective of diagnostic accuracy study included 226 patients with various clinical presentations; infertility, recurrent pregnancy loss, menstrual disorders and post-menopausal bleeding with suspected uterine cavity lesions or abnormality on two-dimensional (2D) TVS or hysterosalpingography (HSG). After taking consent, all patients were subjected to history taking, clinical examination, 3D TVS evaluation, magnetic resonance imaging (MRI) and finally endoscopic examination. Results: The 3D has 98% accuracy in infertile women in comparison to 87% for MRI. While with recurrent pregnancy loss, Concordance was 96% correct for 3D and 78% for MRI. The women with abnormal uterine bleeding, the accuracy of 3D was 100%, while with MRI was 74%. The sensitivity of 3D TVS was 97.8% and 100% specificity, positive and negative predictive value. While the sensitivity, specificity, positive and negative predictive values for MRI were 89.3%, 64%, 70.4% and 86.3% respectively. Conclusions: 3D TVS appears to be extremely accurate, less expensive and a rapid examination for the diagnosis and classification of uterine anomalies, more than MRI. Thus it may become the only mandatory step in the assessment of the uterine cavity.